2005
DOI: 10.1029/2004gl021786
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation measurements from sonic waveform logs in methane hydrate‐bearing sediments at the Nankai Trough exploratory well off Tokai, central Japan

Abstract: [1] I have used full waveform logs from the Nankai Trough exploratory well off central Japan to estimate both compressional and shear attenuation in sediments containing methane hydrate (MH). The attenuation estimates are based on a median frequency shift to the amplitude spectrum of the recorded waveforms. This paper is concerned with attenuation at sonic frequencies of 10-20 kHz for compressional waves and 500-1000 Hz for shear waves. I observed that the presence of MH increases the host sediments' seismic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 9 publications
4
24
0
Order By: Relevance
“…From the association of highest Qp with the zone in which, from the locally increased Vp, hydrate concentration is likely to be greatest one might expect the increase in elastic modulii caused by hydrate would also lead to an increase in Q, but this is contrary to the observations of Guerin et al (1999), Guerin and Goldberg (2002) and Matsushima (2005) that Qp is inversely dependent upon hydrate content at sonic frequencies (10-25 kHz). It is consistent, however, with the positive correlation between increased hydrate content and higher Qp obtained at 'seismic' frequencies (30-110 Hz) from VSPs offshore Tokai, Japan (Matsushima, 2006).…”
Section: Inversion For Qp and Qs And The Effect Of Hydrate On Attenuamentioning
confidence: 73%
“…From the association of highest Qp with the zone in which, from the locally increased Vp, hydrate concentration is likely to be greatest one might expect the increase in elastic modulii caused by hydrate would also lead to an increase in Q, but this is contrary to the observations of Guerin et al (1999), Guerin and Goldberg (2002) and Matsushima (2005) that Qp is inversely dependent upon hydrate content at sonic frequencies (10-25 kHz). It is consistent, however, with the positive correlation between increased hydrate content and higher Qp obtained at 'seismic' frequencies (30-110 Hz) from VSPs offshore Tokai, Japan (Matsushima, 2006).…”
Section: Inversion For Qp and Qs And The Effect Of Hydrate On Attenuamentioning
confidence: 73%
“…It has also been shown that seismic frequency content is reduced below gas-bearing sediments and the presence of gas hydrate also reduces the frequency content and increases seismic attenuation in both marine and permafrost settings (e.g. Sain et al, 2009;Guerin and Goldberg, 2002;Bellefleur et al, 2007;Matsushima, 2005Matsushima, , 2006. Thus the instantaneous seismic frequency attribute may highlight zones that are affected by either gas hydrate or free gas by showing reduced attribute values.…”
Section: Lateral Extent Of the Fractured Systemmentioning
confidence: 99%
“…Laboratory experiments in hydrate bearing sediments indicated increase of attenuation with hydrate saturation (Priest et al, 2006;Best et al, 2013), whereas attenuation estimates from field experiments on gas hydrates indicated contradicting results. For example, studies on well-log data Goldberg, 2002, 2005;Matsushima, 2005), vertical seismic profile (VSP) data Bellefleur et al, 2007), and on crosshole seismic data (Pratt et al, 2003;Bauer et al, 2005) indicated an increase in attenuation. Other studies, mainly on surface seismic data (Matsushima, 2006;Rossi et al, 2007;Dewangan et al, 2014) indicated a decrease in attenuation.…”
Section: Introductionmentioning
confidence: 99%